The Effect of Seed Sources Variation and Presowing Treatments on the Seed Germination of Acacia catechu and Elaeocarpus floribundus Species in Bangladesh - Niamjit Das (International Journal of Forestry Research)
The seed germination of seed sources and presowing treatments of Acacia catechu and Elaeocarpus floribundus seeds were conducted in the nursery of Bangladesh Agricultural University. The seeds were collected from matured and healthy trees from four different locations in Bangladesh and treated with six presowing methods. The germination test was conducted in polybags with a mixture of topsoil and cow dung in a ratio of 3 : 1. The results of ANOVA showed no significant differences among seed sources but statistically significant differences among the presowing treatments for both species. Thus the presowing methods affected the germination process of seeds, and then the highest germination success was found to be 91.26% in hot water (80°C for 10 min), treatment in Acacia catechu and the highest germination success (89.81%) of Elaeocarpus floribundus was found in H2SO4 treatment followed by 86.35% and 78.42% in treatments with hot water (100°C for 12 min) and scarification. The study also revealed that the interactions between seed source variation and presowing methods effect significantly differed in seed germination percentages. Therefore, it is concluded that hot water treatment can be suggested on seed germination of both species for developing nurseries and rural Bangladesh.